Timing, internal flow characteristics, and emplacement mechanisms of the intrusive sheet network on the southern margin of Mount Hillers, Henry Mountains, southern Utah - Thornton, Erik (East Carolina University, 2015)
The exceptional 3-d exposures of the mid-Tertiary intrusive sheet network on the southern margin of Mount Hillers, Henry Mountains, southern Utah, have undergone no syn- or post-emplacement deformation. The sills and dikes, which formed above the underlying Mount Hillers laccolith, therefore provide an ideal opportunity to study purely magmatic processes in a shallow crustal intrusive sheet network. For this study, field work and laboratory analysis were employed to constrain the timing, emplacement mechanisms, and internal flow characteristics of these sills and dikes. Detailed geologic mapping of cross-cutting relationships, in addition to qualitative textural analysis in the field, indicate that younger, relatively fine-grained dikes cross-cut older, relatively coarse-grained sills. Crystal size distribution, thin section petrography, and major and trace element geochemistry all suggest two distinct batches of magma (one coarse- and one fine-grained) were involved in the construction of the sill/dike complex. Field fabrics and anisotropy of magnetic susceptibility fabrics suggest complex internal flow of the intrusive sheets throughout the growth of the central intrusive igneous body. Field observations indicate that intruding magma exploited radial fractures and bedding planes in the sedimentary host rock. In addition, rigidity contrasts in the host rock were likely an important control on the stratigraphic level of sill emplacement and on intrusive sheet thickness. The proposed construction model for the intrusive sheet network consists of an initial phase of dike-fed sill emplacement in subhorizontal strata. During subsequent growth of the underlying main laccolithic body, which included uplift and rotation of the overburden, continued sill emplacement was followed by radial dike intrusion. This work provides insight into the growth and evolution of shallow crustal magmatic systems, such as those that underlie active volcanoes.
Keywords: Geology; Dikes; Emplacement; Magmas; Sills; Intrusions (Geology)--Utah--Henry Mountains; Laccoliths; Magmatism--Utah--Henry Mountains; Geology--Utah--Henry Mountains; Henry Mountains (Utah)